Modelling the effects of spatial and temporal correlation of population densities in a railway transportation corridor - Liu, Ding (European Journal of Transport and Infrastructure Research, 2015)
The existence of spatial and temporal correlation of population densities has been identified in many previous studies. This paper investigates the effects of spatial and temporal correlation of population densities on system disutility in a railway transportation corridor. System disutility is defined as the summation of households disutility. It shows that spatial and temporal correlation of population densities has significant effects on the results of population densities and the system performance measured in system disutility, consumer surplus and social welfare of railway system. Two numerical examples are given to illustrate the properties of the proposed model and its application together with some insightful findings.